Pengaruh Kepuasan Kerja dan Iklim Organisasi Terhadap Organizational Citizenship Behavior OCB Pada Karyawan PT. Aisyah Makmur Sejahtera Pangkalan Kerinci - Elvi Lastriani; Mira Rosmala; Andri Ongki Priyanto (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
Organizational Citizenship Behavior (OCB) is a voluntary action and outside theemployee's role that can make a positive contribution to the development and effectiveness of the organization. OCB is shown, among other things, in the form of altruism, consc ientiousness,sportsmanship, politeness and benevolence. The increase in OCB is influenced by two factors,namely internal factors such as job satisfaction, organizational commitmentThis research aims todetermine the influence of job satisfaction and organizational climate on organizational citizenshipbehavior (OCB) in PT employees. Aisyah Makmur Sejahtera Pangkalan Kerinci. Samples weretaken based on employees of PT. Aisyah Makmur Sejahtera Pangkalan Kerinci using census techniques, namely using the entire population without having to draw a research sample as anobservation unit of 50 people. From the results of instrument testing using IBM SPSS 29, the AdjutedR Square is 0.704 or the determinant coefficient value shows that the Job Satisfaction (X1) andOrganizational Climate (X2) variables on Organizational Citizenship Behavior (Y) are 70.4% while the remaining 29.6% influenced by other factors not discussed in this study.